A one-dimensional flux-based thermography for thermal diffusivity estimation in metallic alloys - Elsheikh, Ahmed (2022)
A Master of Science thesis in Mechanical Engineering by Ahmed Elsheikh entitled, “A one-dimensional flux-based thermography for thermal diffusivity estimation in metallic alloys”, submitted in October 2022. Thesis advisor is Dr. Bassam A. Abu-Nabah and thesis co-advisor is Dr. Mohamed O. Hamdan. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).